PEDAGOGIKA OLIY TA’LIM MUASSASALARIDA O‘QUV FAOLIYATI TAHLILI - Tuxtaxoʻjayev, X.B. (SCIENCE and SOCIETY, 2025)
The article examines the characteristics and factors affecting the educational activity of students of pedagogical universities. The study is aimed at identifying problems and identifying ways to improve the effectiveness of the educational process. The methods used were questionnaires, observation and analysis of educational documents. As a result, it was found that students' educational activity is significantly affected by motivation, organization of the educational process and interaction with teachers. Recommendations are offered for optimizing educational activity in the conditions of a higher pedagogical school.
Keywords: educational activity; pedagogical university; motivation; educational process; professional training; active teaching methods